PSII-28 Impact of commingling on feedlot steer productivity - Hubbard, Amanda J (J Anim Sci, 2019)
This study evaluated the impact of commingling two sources of cattle on productivity during the feedlot phase of production. Angus crossbred steers (n = 96), similar in genetic composition and age, from two research stations (n = 48 McG and n = 48 BCS) were transported (833.64 ± 85.29 km) to a feedlot 39-d prior to study commencement. Steers were blocked by source and stratified by d -34 body weight (BW) before being randomly assigned to one of 12 pens (n = 8 steers/pen) for the 42-d study. Pens were assigned to one of two treatments (n = 6 pens/treatment): 1) NOMIX—100% of cattle from either McG (n = 3 pens) or 100% of cattle from BCS (n = 3 pens) and, 2) MIX—50% of cattle from BCS and 50% from McG (n = 6 pens). Body weight was collected on d0, on d24, and at the end of the study on d42. Orthogonal contrasts analyzed effects of commingling (NOMIX vs. MIX) and source (BCS vs. McG) on dry matter intake (DMI), average daily gain (ADG), and gain to feed (G:F). Linear mixed models (PROC MIXED) evaluated impact of source × treatment on ADG. No effects of commingling (P > 0.05) or source (P > 0.05) were detected on DMI (MIX 8.25, BCS 8.70, McG 8.14 kg/steer/day), ADG (MIX: 1.48, BCS: 1.67, McG: 1.59 kg/steer), and G:F (MIX: 0.18, BCS: 0.19, McG: 0.19). There was no effect of source × treatment on ADG (P > 0.05); however, McG-MIX had the smallest ADG (1.42 kg/steer) compared to BCS-MIX, BCS-NOMIX, and McG-MIX (1.61, 1.59, and 1.60 kg/steer, respectively). Source and mixing treatment did not statistically impact productivity or efficiency, however, mixed cattle were numerically less productive than non-mixed cattle, and the impact of mixing on productivity may vary by source.